Development of ceramics cutting tool for machining using aluminium oxide reinforced with copper powder - Muhammad Aiman, Ishak (2016)
Powder metallurgy (processing) method was used to produce an insert for machining application. An alumina (Al2O3) powder reinforced with Copper power was used as a raw material. A complete die was produced for the insert production. Powder mixing, compaction and sintering using open air furnace were the main processing parameters in the research project. The composite insert was analyzed for density and hardness properties. The result showed that 90% of the theoretical density was achieved and 70% by weight mixed with 30% copper was measured for the higher Vickers hardness value.